2006
DOI: 10.1116/1.2348731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods to contact to nanowires

Abstract: A comparison of four different methods to make electrical contact to both 100nm gold nanowires and 50nm multiwall carbon nanotubes is given. The techniques are compared in terms of the success yield, contact resistance, complexity of the fabrication steps, and potential for creating novel device structures and architectures. The different methods compared are (i) in situ micromanipulation of wires onto prepatterned electrodes, (ii) ion and electron beam assisted deposition, (iii) electron beam lithography, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
2
25
1
Order By: Relevance
“…One-dimensional (1D) nanostructures, especially nanowires with high aspect ratios, have attracted much attention due to their potential applications, such as interconnects in nanofabrication [1], optoelectronics [2], nanosensors [3], nano-biotechnology [4], and electron emitters [5,6]. With the development of nanodevices, the study of thermal expansion properties of 1D nanomaterials has become the focus of intensive research.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional (1D) nanostructures, especially nanowires with high aspect ratios, have attracted much attention due to their potential applications, such as interconnects in nanofabrication [1], optoelectronics [2], nanosensors [3], nano-biotechnology [4], and electron emitters [5,6]. With the development of nanodevices, the study of thermal expansion properties of 1D nanomaterials has become the focus of intensive research.…”
Section: Introductionmentioning
confidence: 99%
“…5 Consequently, there has been a growing interest in the use of random nanowire networks (NWNs), 6,7 where placement is not important and differences in properties are averaged out. These advantages, in combination with superior mechanical performance 8 and the ability to spray-deposit networks over large areas, 9 have extended potential applications to include transparent, flexible conductors 8,10 or even artificial skin.…”
mentioning
confidence: 99%
“…
Nanostructures, especially nanowires with high aspect ratios, have attracted much attention due to their potential applications, such as interconnects in nanofabrication, [1] optoelectronics, [2] nanosensors, [3] nano-biotechnology, [4] and electron emitters. [5][6][7] It was reported that the properties of the nanostructures were affected by their size and morphology, [8][9][10] which subsequently prompted extensive efforts to control them.
…”
mentioning
confidence: 99%